Innovative Laser Alarm System for Enhanced Home Security and Burglary Prevention - Insaan, Nashiirotul; Maulana, Yusuf; Rengga, Nikodemos; Junantoro, Hagai; Rifky, Raja; Pradana, Afu Ichsan (LPPM STIKI Malang, 2024)
The purpose of this research is to design and develop a laser-based alarm system that produces sound when the laser beam is interrupted, aiming to prevent theft. The research methods include literature study, design, and device development. The results show that this laser-based security system can detect shadow movement using a light sensor and a microcontroller. Therefore, the laser alarm system can be effectively used to detect suspicious movements and provide alerts when the laser beam is disrupted. Further development of this system can be carried out to enhance its reliability and application in various security fields.